Aggregation, Cytotoxicity and DNA Binding in a Series of Calix[4]arene Amphiphile Containing Aminotriazole Groups - Diana Mironova; Egor Makarov; Islamiya Bilyukova; Kevser Akyol; Elsa Sultanova; Vladimir Evtugyn; Damir Davletshin; Elvina Gilyazova; Emil Bulatov; Vladimir Burilov; Svetlana Solovieva; Igor Antipin (MDPI AG, 2023)
The present work focuses on the study of the aggregation and complexing properties of calixarenes as potential DNA condensation agents for gene delivery. In the current study, 1,4-triazole derivatives of calix[4]arenes 7 and 8 containing monoammonium fragments were synthesized. The synthesized compound's structure was characterized by using various spectroscopic techniques (FTIR, HRESI MS, ¹H NMR and ¹³C NMR). The interactions between a series of calix[4]arene-containing aminotriazole groups (triazole-containing macrocycles with diethylenetriammonium fragments (3 and 4) and triazole-containing macrocycles with monoammonium fragments (7 and 8)) and calf thymus DNA were carried out via UV absorption, fluorescence spectroscopy, dynamic light scattering and zeta potential measurements. The role of the binding forces of calixarene-DNA complexes was analyzed. Photophysical and morphological studies revealed the interaction of the calixarenes 3, 4 and 8 with ct-DNA, which transformed the fibrous structure of ct-DNA to completely condensed compact structures that are 50 nm in diameter. The cytotoxic properties of calixarenes 3, 4, 7 and 8 against cancerous cells (MCF7, PC-3) as well as a healthy cell line (HSF) were investigated. Compound 4 was found to have the highest toxic effect on MCF7 breast adenocarcinoma (IC50 3.3 μM).